Lingkungan Kerja, Beban Kerja, Dan Kinerja Karyawan Serta Kepuasan Kerja Sebagai Variabel Intervening - Kridho Hery Gunawan; Nabilla Hayatun Nufusi (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to determine the effect of work environment and workload on employee performance through job satisfaction as an intervening variable at PT. Pegadaian Wiyung Surabaya Branch. The population in this study is the company PT. Surabaya Wiyung Branch Pawnshop. The research method is assisted by the Partial Least Square program which is used with SmartPLS 4.0 software. This type of research used is quantitative research. Data taken using a questionnaire. The results showed that the work environment has a positive and significant effect on employee performance, workload has a positive and significant effect on employee performance, work environment has a positive and significant effect on job satisfaction, workload has a negative and insignificant effect, and job satisfaction has employee performance has a negative and insignificant effect,work environment has a negative and insignificant effect through job satisfaction on employee performance at PT. Pegadaian Wiyung Surabaya Branch, and workload has a negative and insignificant effect through job satisfaction on employee performance at PT. Pegadaian Wiyung Surabaya Branch.